Polydopamine-Enabled Approach toward Tailored Plasmonic Nanogapped Nanoparticles: From Nanogap Engineering to Multifunctionality - Zhou, Jiajing (2017)
We present a platform strategy that offers diverse flexibility in tailoring the structure and properties of core–shell plasmonic nanoparticles with built-in nanogaps. Our results have demonstrated that polydopamine serves multiple concerted functions as a nanoscale spacer to afford controllable nanogap sizes, a redox-active coating to promote metal shell growth, and a reactive scaffold to exclusively lock molecular probes inside the nanogap for surface-enhanced Raman scattering (SERS). More interestingly, the universal adhesion of polydopamine on diverse colloidal substrates allows for customized synthesis of multishell plasmonic nanogapped nanoparticles (NNPs) and multifunctional hybrid NNPs containing different cores (i.e., magnetic nanoparticles), which are not readily accessible by conventional methods. Internally coupled plasmonic NNPs with broadly tunable spectroscopic properties, highly active SERS, and multifunctionality hold great promise for emerging fields, such as sensing, optoelectronics, and theranostics, as demonstrated by the ultrasensitive SERS detection and efficient photothermal killing of food-borne pathogens here.